The Audit of Governance Information Technology Services Using ITIL v3 Focuses on Service Operation Domain in Institution X - Putu Sri Merta Suryani; dwi ardiada; I Gusti Ngurah Janardana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Abstract-Information technology is currently growing very rapidly. Almost all agencies take advantage of the role of information technology. In the X agencies engaged in the social field of information technology as a goal that must be achieved. In order to create good government, an agency must be supported by good IT governance in order that information technology and business objectives are aligned and have added value for the agency. This study aims to measure the governance of IT services. This research is done because the agency X is now using IT services. The existence of good policies and procedures on the insight X can create a good service as well. This study uses the ITIL v3 framework that focuses on Service Operation domain. The ITIL framework is an IT services management guide. Measurement of maturity level using COBIT. The level of maturity in this governance audit is at level 3. Recommendations are given to achieve the expected targets within the ITIL framework. Keyword- Audit, ITIL V3, COBIT, IT Services